РИНОК ПРАЦІ УКРАЇНИ: РЕАЛІЇ, ПРОБЛЕМИ І ПЕРСПЕКТИВИ РОЗВИТКУ (International Journal of Innovative Technologies in Economy, 2018)
The article represents the research of the current state of the labor market in Ukraine. In particular, the article deals with such important aspects as the employment level, remuneration level, migration processes. The main obstacles to the successful labor market development are identified. The causes of unemployment in Ukraine are highlighted. The research also focuses on the growing problem of labor migration from Ukraine to the European Union. The study identifies the problem of youth employment, namely, after achieving higher education. The study sees into the analysts' forecasts concerning the tendencies of the increasing demand for certain specialties. The authors explore the main trends and forecasts for the human capital market development in 2018. The article offers some ways of activating labor relations in the economic life of the country, both from the point of view of the state policy and employers.